2008
DOI: 10.51200/ljms.vi.2972
|View full text |Cite
|
Sign up to set email alerts
|

Banking Channels Adoption in Malaysia: An Analysis

Abstract: The purpose of this paper is to examine the factors that affecting Malaysian bank customers acceptance of banking channels namely branch banking, ATM banking, telephone banking and Internet banking. Considering this objective in mind, the current study tends to develop a model, a theoretical framework that explains the factors affecting banking channels adoption from a Malaysian point of view. The model was tested with a survey sample (n = 241). Results suggest that convenience factors are the most influential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In his study on the Jordanian banking sector involving 11 out of 17 banks, one of the most important roles of BCM is to provide customers with uninterruptible and secured banking services at all time. The finding is consistent with the result of a study by Supinah, Anis and Amin (2008) which discovered that stability and service assurance are the essential factors impacting Internet banking adoption. Similarly, a study by Suki, Atrianedi and Suki (2009) also revealed that service reliability is a crucial factor for consumer when using SMS banking.…”
Section: Organizational Performance and Bcmsupporting
confidence: 91%
“…In his study on the Jordanian banking sector involving 11 out of 17 banks, one of the most important roles of BCM is to provide customers with uninterruptible and secured banking services at all time. The finding is consistent with the result of a study by Supinah, Anis and Amin (2008) which discovered that stability and service assurance are the essential factors impacting Internet banking adoption. Similarly, a study by Suki, Atrianedi and Suki (2009) also revealed that service reliability is a crucial factor for consumer when using SMS banking.…”
Section: Organizational Performance and Bcmsupporting
confidence: 91%